PERBANDINGAN PENGGUNAAN KONJUGAT ANTIBOVINE IGG-HRP DAN PROTEIN A/G-HRP DENGAN BEBERAPA LARUTAN PENGENCER SERUM PADA ELISA UNTUK DETEKSI SURRA PADA SAPI DAN KERBAU - Subekti, Didik T.; Yuniarto, Ichwan (Perhimpunan Biologi Indonesia, 2017)
ABSTRACTSurra was reported in various types of animals both livestock, pets and wildlife. ELISA (enzyme linked immunosorbentassay) is a sensitive and specific diagnosis technique for Surra detection. The use of speciesspecific conjugate (anti bovine IgG-HRP) has limited while protein A/G can be used for a wide variety of animalspecies. This study aimed to evaluate the initial application of the protein A/G-HRP compared with antibovine IgG-HRP using standard samples using four (4) types of diluent buffer. The standard serum samples (23serum) consist of positive and negative sera from bovine (cattle and buffalo) were reacted with Surra antigenon microplate. Positive and negative serum was diluted with different diluent buffer, namely PBS-Tween20(PBST), RBA (RedBuff A), RBB (RedBuff B) and LC (Low Cross). Results of ELISA using protein A/G-HRPshowed absorbance values reduced 36.16% - 69.30% compared to the anti-bovine IgG-HRP. The percentagereduction of PBST, RBA, RBB and LC, were 51.76%; 56.64%; 36.16% and 69.30% respectively. The use ofprotein A/G-HRP and fourth diluent buffer can reduce antigen - antibody bonding with a weak affinity whichlowers the absorbance value of ELISA Surra.Keywords : Protein A, Protein G, Surra, ELISA, Trypanosoma evansi